The Place of Ethical Subjectivism in Nietzsche and Levinas’s Thought - Bayan Karimy; Mohamad Asghari (Pizhūhish/hā-yi Falsafī- Kalāmī, 2020)
Nietzsche and Levinas are the most prominent contemporary philosophers who have emphasized on the necessity of passing over rational subjectivity. They tried to rethink the meaning of ethics in a world where neither religion nor other moral philosophies could create a strict and reliable source for the crisis of the contemporary human being. In an attempt to overcome rational subjectivism, Nietzsche and Levinas redefined concepts such as morality and the subject. The purpose of the paper is to describe the attitudes of Nietzsche and Levinas towards their critiques of rational subjectivism. Then examine Nietzsche’s naturalistic reading and Levinas’ transcendental reading of the subject and their encounter with the other and also introduce their critiques of traditional ethics and propose a new kind of ethics in their thoughts. We will then evaluate their alternative concepts in the problem of overcoming rational subjectivism and finally, we will compare these two attitudes. Although Nietzsche and Levinas initially adopted common points of view for the critique of subjectivism and traditional ethics and common criticisms in the field, they presented different results, goals, and methods. Based on these approaches, each has proposed different principles and conclusions about ethics and overcoming rational subjectivism. Nietzsche’s problem is the genealogy of values, and Levinas’s question is the possibility of a moral condition. The answer to the first question is not related to the second question. The present paper shows that both Levinas and Nietzsche have presented different insights into the meaning of subjectivity. Their efforts to find the meaning of subjectivity have also been accompanied by the necessity to destruct the meaning of morality. Accordingly, by focusing on the overman (Nietzsche) and the other (Levinas), they have sought to reevaluate values ​​(Nietzsche) and asymmetric moral responsibility (Levinas). In this regard, they have adopted a completely different view from the traditional view of ethics. Although both of them start with a common point of view, their methods, interpretations, and results are different. With a genealogical approach, Nietzsche considered the will of power in the active subject and the birth of the overman to be desirable and practical to end the history of the development of nihilism. And Levinas, with a phenomenological approach to the concept of asymmetric responsibility in the passive subject, has put an end to the history of neglect of the other and rational subjectivism. The final suggestion is that Nietzsche and Levinas are both looking for a new meaning of morality that resides not in the mind but in the body. In Levinas, the relationship between the body and morality is evolving and transcendental, with concepts of responsibility and suffering, but in Nietzsche, this kind of connection fluctuates between naturalistic and transcendentalist views and considers the concepts of power and instinct important. Nietzsche’s attitude about the human being is a combination of a naturalistic and over-humanist approach, and with the precedence of selfhood, he has expressed a negative view of the other. However, Levinas’ philosophy is more humanistic and inter-subjectivity because of ethical ideals, and ethics begin with recognition of the priority of the other.